Mutation induction of chrysanthemum (dendranthema grandiflora tzvelev) using gamma and ion beam irradiation - Salleh, Shakinah (2013)
Chrysanthemum is one of the major temperate cut flowers in Malaysia. In chrysanthemum production, there is always a demand for new cultivars with varied flower colours and shapes coupled with other preferred traits. Induced mutation using physical mutagens including gamma ray and ion beam in combination with in vitro propagation can be used to generate variations in ornamental plants. The present study was conducted to generate variations in chrysanthemum to produce new cultivars through nuclear technology in combination with plant biotechnology techniques. In establishing the protocol for in vitro propagation, ray florets were cultured on Murashige and Skoog (MS) medium containing five levels of α–naphthaleneacetic acid (NAA) (0, 0.2, 0.5, 1.0 and 2.0 mg/L) and four levels of 6-benzylaminopurine (BAP) (0, 0.5, 1.0 and 2.0 mg/L). Optimum concentration for callus initiation occurred in medium with 0.5 mg/L NAA + 0.5 mg/L BAP while the concentration for shoot regeneration was optimum in MS medium with 0.5 mg/L NAA + 2.0 mg/L BAP. The highest number of normal shoots was also obtained in medium with 0.5 mg/L NAA and 2.0 mg/L BAP. Medium NAA at 0.5 mg/L + BAP at 0.5 mg/L was established as optimum for callus induction from ray florets explants. Subsequent subcultures were done in medium with 0.5 mg/L NAA and 2.0 mg/L BAP for shoot development. A radiosensitivity (radiation sensitivity) test was carried out to determine the optimum dose for mutation using acute gamma (0 to 120.0 Gy) and ion beam (0 to 30.0 Gy) for two types of explants (ray florets and nodal explants) based on their in vitro survival and shoot regeneration. The results showed that the optimum dose for mutation induction of ray florets explants using acute gamma was less than 41.36 Gy and the corresponding dose for ion beam was less than 10.48 Gy. The shoulder dose for irradiated ray florets explants using acute gamma and ion beam were approximately 10.0 and 2.0 Gy,respectively. The optimum dose for mutation induction of nodal explants using acute gamma and ion beam was less than 43.33 and 10.32 Gy,respectively. The shoulder dose for irradiated nodal explants using acute gamma and ion beam were approximately 10.0 and 3.0 Gy, respectively. The result suggests that the relative biological effectiveness (RBE) for ray florets and nodal explants was 3.95 and 4.20, respectively. The in vitro propagated plantlets were grown in Cameron Highlands,Malaysia (elevation: 1500 m) to evaluate the changes on morphological and flowering characteristics of plants. 16 categories of plants were established in the field: Those derived from ray florets – acute gamma treatment (10.0 and 20.0 Gy) and ion beam treatment (0.5, 1.0 and 2.0 Gy); plants derived nodal explants - acute gamma treatment (10.0, 20.0, 30.0, 40.0 and 60.0 Gy) and ion beam treatment (0.5, 1.0, 2.0, 3.0, 5.0 and 8.0 Gy). Results showed that the ion beam totally altered the plant morphology and flowering characteristics (except the response time) of plants derived from ray florets explants. Acute gamma only altered the flowering characteristics (except the response time). Leaf characteristics were altered by both mutagens. Both acute gamma and ion beam did not alter the morphology of plants derived from nodal explants but showed marked differences in the flowering characteristics especially on the number of buds and flower colours. Both mutagens altered the leaf characteristics such as leaf colour, blade length and shape. In conclusion, ray florets explants are more sensitive to both types of physical mutagens as compared to nodal explants. Ion beam was found to be more effective than acute gamma in inducing mutations for Dendranthema grandiflora cv. ‘Reagan Red’.